GE_GERICHTE C/2595/2018 vom 5. Oktober 2021 - GE Cour de justice (2021)
SUCCESSION;INVALIDATION CONVENTION DE CESSION ACTIONS;ENRICHISSEMENT ILLEGITIME;LEGITIMATION ACTIVE;CONSORITE NECESSAIRE | CPC.70.al1; CC.602; CC.659